A General Overview on Non-coding RNA-Based Diagnostic and Therapeutic Approaches for Liver Diseases - Sanchari Roy; Christian Trautwein; Tom Luedde; Christoph Roderburg (Frontiers Media S.A., 2018)
Liver diseases contribute to the global mortality and morbidity and still represent a major health problem leading to the death of people worldwide. Although there are several treatment options available for Hepatitis C infections, for most liver disease the pharmacological options are still limited. Therefore, the development of new targets against liver diseases is of high interest. Non-coding RNA (ncRNA) such as microRNA (miRNA) or long ncRNA (lncRNA) have been shown to be deeply involved in the pathophysiology of almost all acute and chronic liver diseases. The emerging evidence showed the potential therapeutic use of miRNA associated with different steps of hepatic pathophysiology. In the present review, we summarize emerging insights of ncRNA in liver diseases. We also highlight example of ncRNAs participating in the pathogenesis of different forms of liver disease and how they can be used as potential therapeutic targets for novel treatment paradigms. Furthermore, we describe an overview of up-to-date clinical trials and discuss about its future in clinical applications. Finally, we highlight the role of circulating ncRNAs in diagnosis of liver diseases and discuss the challenges and drawbacks of the usage of ncRNAs in clinical setting.